Application of Securitization of Leasing Assets - I. V. Linev (MGIMO University Press, 2014)
Securitization of leasing assets was widely adopted abroad within the last decades. Securitization of leasing assets usually is meant as process of formation of a portfolio based on future leasing payments of one and (or) more leasing company and sale of securities to investors for the subsequent refinancing of leasing operations. These securities can be bonds, actions or bills. Thus the asset leased, acts as providing these papers. Nomenclature of property includes office, medical (first of all, stomatology), training, video the equipment, and also a car, motor-equipment, towers of cellular communication production of heavy mechanical engineering and computers. The essence of securitization of leasing assets consists in isolation of streams of leasing payments from risk of bankruptcy of the leasing company. As the considered mechanism has the greatest development in the USA, so far as consideration of experience of its application in this country is represented especially actual. The special attention is deserved by a question of decrease in credit risk of the investor. External and internal providing is applied to its decision in different types. Interest of participants in securitization of leasing assets consists in distribution of risks between them, emergence of a new source of financing, depreciation of attracted resources, increase of liquidity of a leasing portfolio and optimization by management by balance of the enterprise. Appeal of this tool to the leasing company in a case when it has no available own funds for business development, represents separate interest. Securitization allows the leasing company to expand sources of attraction of the capital and to receive a reserve for the future, and also to broaden the sphere of options of activity and to give it new opportunities for financing of projects. Widespread introduction of schemes of securitization in practice of the Russian leasing business, requires development, and on some aspects -creation of the corresponding legislative base. In the conditions of a tendency observed around the world to broad use of this tool, which gives a powerful impulse to development both bank, and real to sectors, Russia cannot stand aside from this process.